TIRE WASTE AS A POTENTIAL MATERIAL FOR CARBON ELECTRODE FABRICATION: A REVIEW - Ahmad Ariri; Sagir Alva; Siti Aishah Hasbullah (Universitas Mercu Buana, 2021)
Nowadays, tire waste is a big issue since the rapid growth of vehicle population worldwide. The disposal of tire waste should be done properly due to the environmental impact caused by stockpile the tire waste in landfill. Many kinds of research had been conducted to dispose of tire waste efficiently for getting valuable material from tire waste by using pyrolysis technology; one of them is carbon. In this review paper, production and application of carbon from tire waste presented. In several studies, carbon derived from tire waste was used as an adsorbent, electrode in energy storage application, like batteries and fuel cell.